ANALISIS IMPLEMENTASI AKAD SYIRKAH PADA PRAKTIK KERJASAMA BAGI HASIL USAHA BUDIDAYA UDANG VANAME - Daniel El Qori (MIYAH : Jurnal Studi Islam, 2020)
Abstract: Fisheries and agriculture are the main sectors of economic support for Indonesian society. Both are also very fundamental factors, so they are regulated in a separate ministerial institution. But unfortunately, industrial development has gradually resulted in the decline in agricultural and fisheries land. Much land has been converted into factories, warehouses and residential areas. Meanwhile, the remaining land is sometimes owned by people who are not interested in engaging in fisheries and agriculture. On the other hand, there is a group of people who are interested in this field and have qualified expertise but have limitations in the form of land. In Banyuajuh Village, Kamal District, Bangkalan Regency, there are many collaborative practices between capital owners, pond land owners, and irrigation managers. They both spend capital and energy in this collaboration, and the profits from shrimp farming will be shared between three parties. The character of this collaborative practice is similar to the syirkah contract in muamalah fiqh. In this study discussed the application of the terms and conditions of the syirkah contract in the practice of sharing the results of shrimp farming in Banyuajuh Village, Kamal District, Bangkalan Regency.Keyword: syirkah, Profit Sharing, fiqh muamalah.